Development of electronic diagnostic system for improving the diagnosis reliability of passenger car brakes - Ravluyk, Vassyl; Derevianchuk, Iaroslav; Afanasenko, Igor; Ravluyk, Nikolay (Eastern-European Journal of Enterprise Technologies, 2016)
The mathematical model that allows determining the pressure in the brake cylinder, distributor chambers and auxiliary reservoir of the car depending on the absolute pressure changes in the air flow through the throttle openings for a scheduled time is developed in the paper for diagnosing the parameters of the brake system of the individual car or train. It is embedded in the hardware-software system algorithm. This allows simulating the operation of the serviceable brake equipment and provides a high accuracy of identifying the diagnostic features of the technical condition of pneumatic systems of passenger cars. The modern system of remote control of the passenger train brakes, which allows remote control of the brake equipment of the train and individual car during travel or at stops at the section and intermediate stations, is developed. The experimental data, recorded during the monitoring of basic parameters of the brake equipment by the electronic diagnostic system of car brakes are checked for the adequacy with the analytical data by the mathematical model. Their correlation is proved.